KELAYAKAN REPLANTING KARET PADA KONDISI MUTU BOKAR DAN HARGA JUAL YANG RENDAH DI KABUPATEN MUARA ENIM SUMATERA SELATAN - Riswani Riswani; Yunita Yunita; Henny Malini; Thirtawati Thirtawati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The current rubber price fluctuation with downward trend, makes rubber farmers in South Sumatra experience a dilemma to carry out replanting. The majority of rubber plants that are more than 25 years old must be replanted because productivity decreases, if not done, farmers can lose their livelihoods because rubber farming is the main livelihood. This condition is the background of this study which aims to describe the rubber farming that is now being carried out by farmers in conditions approaching replanting and relatively low prices that have an impact on the quality of the Bokar, as well as analyzing the feasibility of rubber commodities from technical, management, marketing and financial aspects. The survey research was conducted in Muara Enim Regency as one of the rubber center areas in South Sumatra, primary data collection was conducted by interviewing 50 respondents who were randomly selected. Data processing is done by qualitative analysis methods, and followed by a feasibility analysis using the eligibility criteria of B / C ratio, R / C ratio, NPV, IRR, Payback ratio and BEP calculation, followed by sensitivity analysis. The analysis shows that the rubber plantation and Bokar processing undertaken by farmers has not followed the recommended rubber farming and Bokar processing, and although the current price conditions are still relatively low, it is still feasible to be undertaken as evidenced by all the values of the business feasibility criteria being in the feasible criteria, so replanting is still recommended for rubber plants that are no longer productive